A Case of Squamous Cell Carcinoma of Conjunctiva as Initial Sign of Systemic Cancers. (29th December 2011) - Mitamura, Hayato; Oshitari, Toshiyuki; Kimoto, Ryuta; Yotsukura, Jiro; Asanagi, Kaoru; Baba, Takayuki; Takahashi, Yoko; Kishimoto, Takashi; Yamamoto, Shuichi
Abstract : The purpose of this report is to present the findings in a case of squamous cell carcinoma (SCC) of the conjunctiva which was the initial sign of systemic cancers. A 94-year-old woman without known systemic diseases developed a mass in her right conjunctiva. She was referred to our hospital 5 months after the onset. She was diagnosed with conjunctival SCC by biopsy. Systemic CT before the surgery revealed multiple liver lesions, lung legions, and a large mass surrounding the appendix. The patient requested the surgery, and the main aim of the surgery was cosmesis. Histopathological examinations of the specimen led us to the final diagnosis as SCC. She did not receive any other therapy because of her age. As no other surgical procedures were undertaken, it is uncertain as to whether the conjunctival lesion was primary or secondary. Although, it is extremely rare that SCC of the conjunctiva is the initial sign of systemic cancers, careful systemic examinations to find other cancers should be made.